Use of oral anticoagulants among individuals with cancer and atrial fibrillation in the United States, 2010–2016. Issue 5 (14th April 2022) - Ardeshirrouhanifard, Shirin; An, Huijun; Goyal, Ravi K.; Raji, Mukaila A.; Segal, Jodi B.; Alexander, G. Caleb; Mehta, Hemalkumar B.
Abstract: Background: Anticoagulation among patients with cancer and atrial fibrillation is challenging due to elevated risk of bleeding and stroke. We characterized use of oral anticoagulants among patients with cancer and non‐valvular atrial fibrillation (NVAF). Methods: We used Surveillance, Epidemiology, and End Results (SEER)‐Medicare data and included patients with cancer aged ≥66 years with an incident diagnosis of NVAF from 2010 to 2016. We used a Cox proportional hazard model and multivariable logistic regression to identify factors associated with anticoagulant use versus no use and direct oral anticoagulants (DOACs) versus warfarin use, respectively. Results: Of 27, 702 patients with cancer and NVAF, 4469 (16.1%) used DOACs and 3577 (12.9%) used warfarin. Among 8046 anticoagulant users, DOACs use increased from 21.8% in 2011 to 76.2% in 2016, with a corresponding decline in warfarin use from 78.2% to 23.8%. Nearly 7 out of 10 patients with cancer and NVAF did not initiate anticoagulation in 2016. Anticoagulant use was more likely among those with higher CHA₂DS₂‐VASc scores (hazard ratio [HR] 1.55, 95% confidence interval [CI] 1.27–1.90 for score ≥6 vs. 1) or with lower HAS‐BLED scores (HR 1.96, 95% CI 1.67–2.30 for score 1 vs. ≥6). Among anticoagulant users, DOAC use was less likely than warfarin in those with higher CHA₂DS₂‐VASc scores (odds ratio [OR] 0.53, 95% CI 0.33–0.84 for score ≥6 vs. 1). Conclusions: Nearly 7 out of 10 patients with cancer and NVAF did not receive anticoagulation. Use of DOACs increased from 2010 to 2016, with a corresponding decline in warfarin use. DOACs are used less than warfarin among those at higher risk of stroke.